2004
DOI: 10.1007/s10832-004-5114-y
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Distributed Loading and Cantilever Angle in Piezo-Force Microscopy

Abstract: Piezo-force microscopy (PFM) is a variation of atomic force microscopy that is widely applied to investigate piezoelectric thin films at the nanometer scale. Curiously, PFM experiments are found to be remarkably sensitive to the position along the cantilever at which deflection is detected, complicating attempts to use this technique to quantify surface actuation and thereby measure the converse piezoelectric coefficient. A straightforward analytical theory is proposed that accounts for this observation by com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 7 publications
2
46
0
Order By: Relevance
“…These non-piezoelectric effects not only hinder accurate PFM measurements but also, in some cases, cumulatively dominate the measured 7 PFM response. [73][74][75] It is therefore very important to acknowledge and understand their influence to allow an accurate interpretation of material properties measured by PFM.…”
Section: Principle Of Pfmmentioning
confidence: 99%
“…These non-piezoelectric effects not only hinder accurate PFM measurements but also, in some cases, cumulatively dominate the measured 7 PFM response. [73][74][75] It is therefore very important to acknowledge and understand their influence to allow an accurate interpretation of material properties measured by PFM.…”
Section: Principle Of Pfmmentioning
confidence: 99%
“…However, the lack of control on mechanical fields results in mostly incomplete information with respect to the separation of the ferroelectric and ferroelastic interfaces, unless complicated threedimensional reconstruction of the domain structure is exploited. [22,23] Therefore, it is imperative to create an approach for local studies of strain-induced phenomena, where external pressure exerted by an SPM probe will directly affect ferroelastic properties of the material during ferroelectric switching.…”
Section: Introductionmentioning
confidence: 99%
“…It was recognized that electrostatic tip-surface forces and buckling oscillations of the cantilever can provide significant and in some cases even dominating contributions to the PFM signal. 17,18,19 Imaging ferroelectric materials in the vicinity of a phase transition at small probing biases or imaging of biological systems with weak electromechanical coupling require optimal imaging conditions to be established, and a number of approaches based on using contact resonances in PFM have been suggested. 20,21 Finally, it is recognized that the use of the cantilever coupled with a beam-deflection detection system typical for most commercial AFM s does not allow longitudinal and normal force components to be unambiguously distinguished, 12,22 and it has been suggested that operation at specific frequencies would allow these components to be differentiated.…”
Section: Introductionmentioning
confidence: 99%